1967
DOI: 10.1143/jjap.6.339
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Emissivity of Silicon

Abstract: The emissivity of silicon was observed in the spectral region from 0.4 to 15 µ at various temperatures from 340°K to 1070°K by using two n-type specimens with the resistivity of 15 ohm-cm and 7×10-3 ohm-cm at 300°K, respectively. The thermal radiation of silicon consists of three types due to band-to-band transition, free carriers and lattice vibration. It was made clear from the emissivity measurement that, in a pure specimen, the radiation due to lattice vibration is conspicuous at low temperatures, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(108 citation statements)
references
References 13 publications
5
102
0
1
Order By: Relevance
“…Radiation thermometry is a typical method meeting this requirement [4], but its accuracy is limited by the uncertainty in the emissivity of the silicon wafer and the thin film layers deposited on the wafer, such as oxide films. The radiative properties of silicon wafers are complex, and change during processing [4][5][6][7][8][9]. In order to overcome this problem, we developed a radiation thermometry method that enables the simultaneous measurement of emissivity and temperature of a silicon wafer, based upon a polarization technique [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation thermometry is a typical method meeting this requirement [4], but its accuracy is limited by the uncertainty in the emissivity of the silicon wafer and the thin film layers deposited on the wafer, such as oxide films. The radiative properties of silicon wafers are complex, and change during processing [4][5][6][7][8][9]. In order to overcome this problem, we developed a radiation thermometry method that enables the simultaneous measurement of emissivity and temperature of a silicon wafer, based upon a polarization technique [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are various absorption mechanisms over a wide spectral range [5,7,[11][12][13][14]. As the wavelength increases, the photon energy decreases until it becomes lower than the minimum energy gap in the silicon band structure.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most prevalent materials for micro electromechanical systems (MEMS), silicon was widely used for manufacturing prototypes of micro-power generating devices and micro-propulsion systems owing to its favourable mechanical and thermal properties [11,13,14]. Moreover, silicon can offer an emissivity of 0.6 -0.7 at elevated temperatures in the convertible band of the PV cells [191], and is therefore considered a reasonable emitter material serving for the purpose of TPV power generation. Table 6.1 has summarised the typical thermal properties of quartz and silicon wafers used in this study.…”
Section: Experiments Setupmentioning
confidence: 99%
“…Satō et al [191] showed that the emissivity for pure silicon specimen first increased as the temperature increased, and then maintained at a constant value (∼0.7 in their work) across the whole IR camera band (7.5 -13 µm) of interest after the temperature increased beyond 870 K. The emissivity for "heavily" doped silicon (doping concentration of ∼8 × 10 18 cm −3 ), however, was found to be much more invariant to the temperature with a band-averaged value of ∼0.75 [191]. The silicon wafers used in this work were described as "lightly" doped by the manufacturer, but the specific doping level was unknown.…”
Section: Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation